2007
DOI: 10.1139/z07-048
|View full text |Cite
|
Sign up to set email alerts
|

Food supplementation experiments revisited: verifying that supplemental food is used by its intended recipients

Abstract: Field-based food supplementation experiments can determine whether populations are limited by natural food availability. However, they may yield spurious results if added food is hoarded by dominants, exploited by immigrants, or delivered ineffectively. Surprisingly, population-level approaches accounting for these potential sources of bias have not been established. We explored responses of free-ranging snowshoe hares (Lepus americanus Erxleben, 1777) to food supplementation by contrasting per capita browsing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…). Another factor potentially biasing experimental studies is the failure to control for individual quality (Wirsing & Murray ). Experiments involve a subsample of individuals and are commonly performed at small spatial scales (i.e.…”
Section: Quantified Effects Of Pafs On Life‐history Traitsmentioning
confidence: 99%
“…). Another factor potentially biasing experimental studies is the failure to control for individual quality (Wirsing & Murray ). Experiments involve a subsample of individuals and are commonly performed at small spatial scales (i.e.…”
Section: Quantified Effects Of Pafs On Life‐history Traitsmentioning
confidence: 99%
“…Although it is difÞcult to experimentally test whether populations of highly mobile consumers are food limited, examining consumer behaviors and patterns of abundance can provide insights into whether consumers have food shortages or surpluses (Petersen et al 2006, Wirsing andMurray 2007). If food is scarce, mobile consumers should have to spend more time foraging and may travel farther to collect sufÞcient resources when resources are exhausted near the nest (Suzuki et al 2007).…”
mentioning
confidence: 99%
“…Critically, however, analysing the data at the individual level, by using PIT tag data to identify which individuals actually used supplementary feed, suggested that food may have had a significant effect at the individual level. The use of supplementary feeding studies to assess the effect of food on population dynamics has been questioned -in particular doubts exist over whether supplementary feed is actually used by the intended recipients, and assessing both individual and population level changes in response to supplementary feeding is a challenge (Boutin, 1990;Wirsing & Murray, 2007). Direct and indirect evidence suggests that not all animals present on fed areas actually use supplementary feed stations (Kenward et al, 2005;Newey et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…An implicit assumption of these experiments is that all individuals in the study population have access to the supplementary food. As such supplementary feeding experiments can be criticized over the unknown extent to which the food reaches the target population, and thus the difficulty of relating both population and individual responses directly to food addition (Boutin, 1990;Wirsing & Murray, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation